DAMPAK DAN PENGARUH PERTAMBANGAN BATUBARA TERHADAP MASYARAKAT DAN LINGKUNGAN DI KALIMANTAN TIMUR - Frendly Albertus dan Yosana Zalukhu (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2019)
A social problem tells of the difficulties, especially a number ofresidents in East Kalimantan to obtain welfare, a healthy environment,and agricultural land that can be used to make a living. Steam powerplant construction projects are one of the causes of coal mining. Where itwill bring the positive side, that the community needs electricity, but onthe other hand will affect the natural resources that are around thedisruption of community activities that are farming and gardening. EastKalimantan is the largest coal producer in Indonesia and has high naturalresource potential. Coal itself is a non-renewable natural resource and ifit is continuously extracted it will affect the environment and waterresources. In the regulation of the Minister of RI No. 26 of 2018, article20 paragraph 2b reads "Prevention and restoration of the environment inthe event of environmental pollution and / or damage". But the data provethat in 2014-2018 it has claimed as many as 115 people due to the minepit. In this case, environmental damage in East Kalimantan, especiallyaround the coal mining area, must take an administrative and educationalapproach, in which the government sanctions legal coal miningentrepreneurs and creates a mining education program to channel ideasand knowledge about sources environmentally friendly energy.